Power Flow Study on Container Crane with Simulation-Based Renewable Energy Supply - Fasha, Dodi; Sarwito, Sardono (International Journal of Marine Engineering Innovation and Research, 2025)
Container port’s loading-unloading process is still using heavy equipment with less eco-friendly fuel. However, currently, several container ports are implementing an eco-friendly port (green port) concept. Renewable natural resources, such as the sun’s heat energy, are used as an alternative to supports the green port concept. Container cranes, the main heavy equipment in the loading and unloading processes, are generally supplied with electricity from PLN and diesel generators. In this research, it was tried by modeling container crane’s one-line diagram into ETAP, but by adding renewable energy resources simulation, such as solar panels. Solar panel’s characteristics, such as voltage and output frequency are different from PLN and diesel generators. Then, the difference results will be analyzed. After the simulation, results in comparison, known that solar panels can be used for container crane’s electrical system supply. In this study, the PV’s inverter output voltage is 0.38 kilo-volt. The PV supply simulation results in lower power efficiency and higher voltage drop than the PLN and diesel generator’s supply. As for each PV supply scenario, power efficiency and drop voltages are still within the IEC and IEEE standard limits. For example, in the gantry scenario, the power efficiency is 94.44%, and the drop voltage is 0.274%.